A critical review of measures of childhood vaccine confidence. (August 2021) - Shapiro, Gilla K; Kaufman, Jessica; Brewer, Noel T; Wiley, Kerrie; Menning, Lisa; Leask, Julie; ,; Abad, Neetu; Betsch, Cornelia; Bura, Vinod; Correa, Gustavo; Dubé, Eve; et al.
Highlights: We identified fourteen measures of childhood vaccine confidence in use globally. Measures were predominantly developed in high-income countries. Use of concepts related to childhood vaccine confidence need greater clarity and consistency. All measures would benefit from additional validation, especially in low and middle-income countries. Public health needs validated measures of childhood vaccine confidence usable in diverse settings that can provide comparable data over time. Abstract : The World Health Organization and global partners sought to identify existing measures of confidence in childhood vaccines, as part of a broader effort to measure the range of behavioural and social drivers of vaccination. We identified 14 confidence measures applicable to childhood vaccination in general, all published between 2010 and 2019. The measures examined 1–5 constructs and included a mean of 12 items. Validation studies commonly examined factor structure, internal consistency reliability, and criterion-related validity. Fewer studies examined convergent and discriminant validity, test-retest reliability, or used cognitive interviewing. Most measures were developed and validated only in high-income countries. These findings highlight the need for a childhood vaccine confidence measure validated for use in diverse global contexts.